Tissue responses after implantation of biodegradable Mg alloys evaluated by multimodality 3D micro‐bioimaging in vivo. Issue 8 (16th February 2021) - Helmholz, Heike; Will, Olga; Penate‐Medina, Tuula; Humbert, Jana; Damm, Timo; Luthringer‐Feyerabend, Berengere; Willumeit‐Römer, Regine; Glüer, Claus‐Christian; Penate‐Medina, Oula
Abstract: The local response of tissue triggered by implantation of degradable magnesium‐based implant materials was investigated in vivo in a murine model. Pins (5.0 mm length by 0.5 mm diameter) made of Mg, Mg‐10Gd, and Ti were implanted in the leg muscle tissue of C57Bl/6N mice ( n = 6). Implantation was generally well tolerated as documented by only a mild short term increase in a multidimensional scoring index. Lack of difference between the groups indicated that the response was systemic and surgery related rather than material dependent. Longitudinal in vivo monitoring utilizing micro‐computed tomography over 42 days demonstrated the highest and most heterogeneous degradation for Mg‐10Gd. Elemental imaging of the explants by micro X‐ray fluorescence spectrometry showed a dense calcium‐phosphate‐containing degradation layer. In order to monitor resulting surgery induced and/or implant material associated local cell stress, sphingomyelin based liposomes containing indocyanine green were administered. An initial increase in fluorescent signals (3–7 days after implantation) indicating cell stress at the site of the implantation was measured by in vivo fluorescent molecular tomography. The signal decreased until the 42nd day for all materials. These findings demonstrate that Mg based implants are well tolerated causing only mild and short term adverse reactions.